2016
DOI: 10.1039/c6fo00122j
|View full text |Cite
|
Sign up to set email alerts
|

Grape powder attenuates the negative effects of GLP-1 receptor antagonism by exendin-3 (9–39) in a normoglycemic mouse model

Abstract: Prediabetes is a condition affecting 35% of US adults and about 50% of US adults age 65+. Foods rich in polyphenols, including flavanols and other flavonoids, have been studied for their putative beneficial effects on many different health conditions including type 2 diabetes mellitus and prediabetes. Studies have shown that some flavanols increase glucagon-like peptide 1 (GLP-1) secretion. GLP-1 is a feeding hormone that increases insulin secretion after carbohydrate consumption, and increased GLP-1 secretion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…Studies have shown that this drug has promising therapeutic effects in the treatment of digestive diseases and diarrhea, but its absorption through oral administration is not satisfactory, and the duration of plasma concentration is short (6,7). Exendin-(9–39), as an antagonist of GLP-1R, can effectively attenuate Nesfatin-1 and delay the emptying of the stomach and reduce the intake of berberine and effectively maintain the retention of berberine (8). In recent years, it has been found that berberine has anti-inflammatory functions and more and more studies confirmed that berberine played a certain regulatory role in inhibiting the body's immune response and anti-apoptosis response (9).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that this drug has promising therapeutic effects in the treatment of digestive diseases and diarrhea, but its absorption through oral administration is not satisfactory, and the duration of plasma concentration is short (6,7). Exendin-(9–39), as an antagonist of GLP-1R, can effectively attenuate Nesfatin-1 and delay the emptying of the stomach and reduce the intake of berberine and effectively maintain the retention of berberine (8). In recent years, it has been found that berberine has anti-inflammatory functions and more and more studies confirmed that berberine played a certain regulatory role in inhibiting the body's immune response and anti-apoptosis response (9).…”
Section: Introductionmentioning
confidence: 99%
“…Since VHFD contains 35% (w/w) fat (see S1 Table ), we reasoned that lipid oxidation could also decrease VHFD palatability and intake. Others have suggested that oxidation of VHFD may occur and that it should avoided [ 5 , 6 ], but this hypothesis has not yet been thoroughly investigated.…”
Section: Resultsmentioning
confidence: 99%
“…may occur and that it should avoided [5,6], but this hypothesis has not yet been thoroughly investigated.…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation